Radiodermatitis in older patients with head and neck cancer (Estima – Brazilian Journal of Enterostomal Therapy, 2025)
Objective: To analyze the incidence of radiodermatitis in older individuals with head and neck cancer undergoing radiotherapy. Method: Observational, prospective, quantitative study. The study included patients aged 60 years or older with head and neck cancer who underwent radiotherapy. Patients were monitored daily during radiotherapy sessions. Skin was assessed using the Acute Radiodermatitis Grading scale, and the occurrence of radiodermatitis and associated signs and symptoms in the irradiated area and skin hydration were recorded. Results: Thirty-three participants were monitored, who were submitted to an average of 33 radiotherapy sessions. Radiodermatitis occurred in 93.9% of participants, with an average dose of 34.7 Gy of ionizing radiation. Symptoms of heat, burning, itching, dry skin, and pain, present in 68% of participants, were reported most often in the fifth week of radiotherapy. Regarding skin hydration, most participants showed a marked imbalance, characterized by low moisture and oiliness. Conclusion: Most patients monitored displayed signs and symptoms of radiodermatitis during radiotherapy sessions. Nurses play a fundamental role in assessing, monitoring the skin, and providing health education on skin care for older patients during radiotherapy, aiming to prevent signs and symptoms of radiodermatitis.